Organizational Change On Employee Performance: Pengaruh Perubahan Organisasi Terhadap Kinerja Karyawan - Lailla, Nor; Mardi (Procedia of Social Sciences and Humanities, 2022)
Along with the current business development, employees are one of the important elements in an organization. Employee performance determines the success or failure of an organization. Therefore, the organization must make internal changes whose impacts tend to affect the work of employees so that they can improve the organization itself. The purpose of this paper is to determine the relationship between organizational change and employee performance. This research methodology uses a Systematic Literature Review (SLR), which is a synthesis of literature research that is carried out by identifying, analyzing, then evaluating through the collection of existing data by searching through research selection. Information used with several international and national journals obtained by screening from Publish or Perish. The benefit of this study is to determine the effect of the relationship between organizational change and employee performance. The results showed that organizational change was related to changes in strategy, culture, employee attitudes, organizational structure, technology, communication leadership, and employee development affecting employee performance.